2002
DOI: 10.1113/jphysiol.2001.013489
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of vasorelaxant responses to anandamide in the rat mesenteric arterial bed

Abstract: The endogenous cannabinoid anandamide has recently been identified as a vasorelaxant but the underlying mechanisms are controversial. The vasorelaxant responses to anandamide have now been examined in the rat mesenteric arterial bed. Anandamide caused potent vasorelaxations (pD2= 6.24 ± 0.06; Rmax= 89.4 ± 2.2 %) which were unaffected by inhibition of nitric oxide synthase with NG‐nitro‐l‐arginine methyl ester (l‐NAME; 300 μm). The responses were also predominantly endothelium independent and were unaffected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 34 publications
(79 reference statements)
8
55
0
1
Order By: Relevance
“…Also, some vessels were incubated for 1 h with the vanilloid agonist capsaicin (10 mM) to deplete the sensory nerves of neurotransmitters. This was followed by a 20-min washout period (Zygmunt et al, 1999;Harris et al, 2002).…”
Section: Experimental Protocolmentioning
confidence: 99%
See 4 more Smart Citations
“…Also, some vessels were incubated for 1 h with the vanilloid agonist capsaicin (10 mM) to deplete the sensory nerves of neurotransmitters. This was followed by a 20-min washout period (Zygmunt et al, 1999;Harris et al, 2002).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…They found that, in isolated mesenteric arteries, vasorelaxation to anandamide was sensitive to the VR antagonist capsazepine, capsaicin pretreatment and CGRP receptor antagonism. A role for sensory nerves in vasorelaxation to CBs has been confirmed since then (Ralevic et al, 2000;Harris et al, 2002), although it is not thought that stimulation of the VR accounts for the entire relaxant response to anandamide (White et al, 2001;Harris et al, 2002;Ho & Hiley, 2003). Since NADA has also been found to stimulate VRs (Huang et al, 2002), their potential involvement in the vasorelaxant response to NADA was investigated.…”
Section: Se O'sullivan Et Al Vasorelaxant Effects Of Nada 807mentioning
confidence: 99%
See 3 more Smart Citations